Implementasi Algoritma PSO untuk Perancangan dan Koordinasi Peredam Osilasi di Sistem Tenaga Listrik dengan UPFC - Sasongko Pramono Hadi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
This paper presents an effective design and coordination of controllers in power system equipped with UPFC. Each controller produce different supplementary signals, the power system stabilizer PSS signal for machine and the power oscillation damping POD signal for UPFC. A single stage lead-lag compensator scheme was considered in the PSS and POD structure. A new computational approach was proposed using PSO algorithm to determine simultaneously the parameter controllers for both PSS and POD. Pole assignment technique was proposed in controller parameter design, the dominant pole should be assigned to locate close to threshold – 0.1. The controller performances were investigated by using 0.2 pu additional load to power system. The simulation results show that both PSS and UPFC POD controller simultaneously present a positive interaction. PSS and POD could enhance dynamic responses performance. The dominant eigenvalues shift and approach their real part threshold. The controllers could give a better rotor angle response, only 4.5 s settling time and the first swing overshoot reduced to 23.38%.